2023
DOI: 10.1007/s12210-022-01131-3
|View full text |Cite
|
Sign up to set email alerts
|

Effect of chilling and salinity stress on photosynthetic performance and ultrastructure of chloroplast in faba beans (Vicia faba L.) leaves

Abstract: Chilling (Ch) and salinity (S) are challenging stresses affecting plant physiology, growth, and productivity. The current study investigated the effects of these two stresses, singly and in combination, on photosynthetic performance and ultrastructure of chloroplast of faba beans (Vicia faba L. Cv. Aspani). Plants were exposed to 3 °C and 120 mM NaCl for 16 h in an optimized soil mixture (sand:clay 2:1) under optimized conditions. Results showed that both Ch and S significantly reduced photosynthetic rates, Fv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 39 publications
1
3
0
Order By: Relevance
“…In the present study, NaCl treatment caused a significant reduction in stomatal index percentage, stomatal area, and opened stomata, which was accompanied by wrinkling and shrinkage of epidermal walls. These findings agreed with those of Mohamed et al [ 50 ], De Micco et al [ 51 ], and El-Dakak et al [ 52 ], who reported reduced stomatal index percentage and stomatal width in different plant species under salinity stress. Additionally, many factors regulate stomatal mechanics, including ABA, NO, specific ions, and water channels [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, NaCl treatment caused a significant reduction in stomatal index percentage, stomatal area, and opened stomata, which was accompanied by wrinkling and shrinkage of epidermal walls. These findings agreed with those of Mohamed et al [ 50 ], De Micco et al [ 51 ], and El-Dakak et al [ 52 ], who reported reduced stomatal index percentage and stomatal width in different plant species under salinity stress. Additionally, many factors regulate stomatal mechanics, including ABA, NO, specific ions, and water channels [ 53 , 54 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the current research, the ultrastructure of the chloroplasts was greatly altered under salinity stress showing distorted thylakoid and an unrecognizable grana structure, which might be brought about by salinity-induced oxidative damage [ 18 , 61 , 62 ] and disturbed ion balance in the chloroplasts [ 63 ]. Similar impacts of salinity stress on the chloroplast structure were observed in cucumber [ 64 ], Arabidopsis [ 65 ], potato [ 66 ], rice [ 67 ], eggplant [ 17 ], and faba bean [ 52 ]. NaCl stress also caused a significant reduction in photosynthetic pigments (chlorophylls and carotenoids): chlorophyll decline might be due to the inhibition of chlorophyll synthesis due to salinity-reduced levels of iron and magnesium, enhanced activity of chlorophyllase by Na + and Cl − accumulation, and/or photoinhibition or ROS toxicity [ 18 , 68 ].…”
Section: Discussionmentioning
confidence: 63%
“…Similarly, Jiang et al [37] reported that CI symptoms of 'Guifei' mango during storage at 5 • C were minor and exhibited a gradual darkening of the peel color with the appearance of small black spots while chilling symptoms of mango turned poorer rapidly after rewarming to 20 • C as severe browning, enlargement of the black spots, depression, and unripeness were observed. In terms of color appearance, this study found that in the CK group, which was severely chilled after 14 days of storage at 4 • C and then at 20 • C for another 6 days, there were still some green coloration, which might result from the chloroplast damage of CI [6,[38][39][40].…”
Section: Discussionmentioning
confidence: 99%
“…This degradation reduces the light energy harvesting area and decreases the total electron yield [ 59 ]. Rehab et al [ 60 ] found that salt stress leads to the deformation of the thylakoid membrane and disintegration of the grana structure, thus reducing the photosynthetic performance of plants. Singh et al [ 61 ] found that nitrate nitrogen sources can protect photosynthetic pigments from ammonium nitrogen stress in tomato leaves, which competitively reduces the absorption of ammonium nitrogen by tomato plants.…”
Section: Discussionmentioning
confidence: 99%